(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
A series of cobalt (II) complexes have been synthesized with Schiff bases derived from ortho-phthalaldehyde and various amines in aqueous methanol solution. The newly synthesized Schiff bases and their Co (II) complexes have been characterizedÂ by elemental analysis, magnetic susceptibility, thermal, conductance measurements, mass, IR, electronic,Â 1H,13C-NMR spectral techniques. These ligands act as tetradentate species and coordinate to the metal center through the different potential donor atoms such as N, O and S. The probable octahedral structures have been assigned to these complexes. All the synthesized Schiff base ligands and Co(II) metal complexes have also been screened for their antimicrobial activities and metal complexes found to be more active than respective Schiff-base ligands.